New Antithrombotic Strategies and Coronary Stent Technologies for Patients at High Bleeding Risk Undergoing Percutaneous Coronary Intervention - Sorrentino, Sabato; Salerno, Nadia; Leo, Isabella; Polimeni, Alberto; Sabatino, Jolanda; Spaccarotella, Carmen A. M.; Mongiardo, Annalisa; De Rosa, Salvatore; Indolfi, Ciro (Current Vascular Pharmacology, 2022)
Patients at High Bleeding Risk (HBR) are a sizable part of the population undergoing Percutaneous Coronary Intervention (PCI) and stent implantation. This population historically lacks standardized definition, thus limiting trial design, data generalizability, and clinical decision– making. To overcome this limitation, the Academic Research Consortium (ARC) has recently released comprehensive guidelines defining HBR criteria for study design purposes and daily clinical practices. Furthermore, several risk scores have been developed aiming to discriminate against HBR patients and support physicians for clinical decision-making when faced with this complex subset of patients. Accordingly, the first part of this review article will explore guideline-recommended risk scoring as well as ARC-HBR criteria and their relative application for daily clinical practice. The second part of this review article will explore the complex interplay between the risk of bleeding and coronary thrombotic events in patients deemed at HBR. Indeed, several features that identify these patients are also independent predictors of recurrent ischemic events, thus challenging revascularization strategies and optimal antithrombotic therapy. Accordingly, several clinical trials have been conducted to evaluate the safety and efficacy of the new generation of coronary platforms and different antithrombotic strategies for HBR patients to minimize both ischemic and bleeding events. Accordingly, in this part, we discuss current guidelines, trials, and observational data evaluating antithrombotic strategies and stent technologies for patients at HBR.
Keywords: DAPT